PROFIL PEREMPUAN BERKELUARGA BEKERJA SEBAGAI DRIVER OJEK ONLINE DI GOJEK KOTA PEKANBARU - Puja Malia Harahap; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Pekanbaru City. The purpose of this study was conducted to determine the profile of women who work as drivers ojek online at Gojek Kota Pekanbaru. This research is a descriptive research using qualitative approach as a tool of analysis. The population in this study were all female students who have married as many as 5 people. Observation data collection techniques, interviews and documentation. Technique of data analysis writer use in this research is descriptive qualitative. The result of the research is their motive for choosing to work as an online motorbike driver because they go on a motorcycle offers an effective and efficient work system where they not only provide technology applications but also recruit to connect drivers with passengers and the conditions for entering gojek are not that difficult. In addition, working hours are not bound, relaxed, but surely there is an income from the female support project working as a motorcycle. Besides, it also helps the economy or adds to their family’s income. Because most of them really like work and don’t like to stay at home. And based on the results of the income that has been obtained that women who work as online motorcycle driver are very potential in supporting the household economy. Because the contribution of income to the family economy is quite large.Keywords: Drivers go Female, Income Contribution, Against Family.